Exploring the barriers and facilitators in the uptake of a novel eMDS (Biodose ConnectTM) used to support medicines adherence - Agbesanwa, Funmi (2021)
As the proportion of the older adult population increases rapidly worldwide, polypharmacy (the prescribing of multiple items to one individual) and consequently medication use continues to increase. Medication non-adherence is contributing to the wider economic burden on health and social services, consequently seeking out practices or methods to improve patients’ adherence to medicines should help to alleviate the issue.